Clients' preference for cueing instrument and style in music therapy - Liu, Bolin, author; LaGasse, Ashley Blythe, advisor; Knight, Andrew, advisor; Choi, Eunhee, committee member (Colorado State University. Libraries, 2019)
Music therapists use different types of cueing instruments (piano, guitar, or autoharp) to facilitate functional outcomes. However, no research has been done to investigate client preference for the facilitation instrument. This study investigated clients' preference for cueing instrument and their perception of how well the music helped them move. The 15 participants were all adults aged 50 and older who participate in music therapy motor rehabilitation groups. Participants completed the responsive survey with some quasi-convenience sampling, and the researcher played six videos that demonstrated cueing with three different instruments (piano, guitar, and autoharp) in two different styles: patterned sensory enhancement (PSE) cueing and simple accompaniment cueing. In the videos, the researcher demonstrated a simple motor movement that is cued with music played on one of the three instruments and in one of the two styles (a total of six conditions). Participants were asked to follow the movements and then answered questions about their instrument preference and their perception of how well the music helped them move. Fifteen participants completed the survey. Based on the data collected, the researcher found that most participants indicated that they felt that the music helped them to move. This may be because different instruments and cueing styles have similar effects on participants or some participants may not perceive any differences between different instruments and cueing styles. Therefore, music was generally acceptable for these participants; however, music therapists should consult with the individual client to learn more about their perception of the music and how they feel it is helping to facilitate their outcomes. Further recommendations include recruiting a larger sample size, counterbalancing the order of the videos, and collecting data on measures of motor movement.